Art in Portland Cement Mortar Pasatiempo Betanzos (A Coruña) - Acuña González, M.ª Teresa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2020)
The purpose of this work, it isto analyze and publicize the works of art built in Portland cement mortar, which formed are Part Pasatiempo Betanzos (A Coruña). This Park was created by D. Juan García Naveira intended to show, perpetuate and pass through the elements of the Pasatiempo, art and culture of other countries. An art that reflected in eclectic style inspired by reinaissance art, classicist, baroque and Art Nouveau. Among the materials most widely used in construction, is portland cement mortar.